Projeto de sistema de aterramento e spda para estrutura edificada: um retrofit aplicado a uma edificação administrativa da UFERSA - Oliveira, Paulo Diego Varelo de (Universidade Federal Rural do Semi-Árido, 2018)
This monograph had as general objective to provide a retrofit in the Pedro Fernandes Pereira building, through the realization of the grounding projects and the System of Protection against Atmospheric Discharges. Edification belongs to Federal Rural University of Semi Arid, Central Campus, Mossoró, Rio Grande do Norte. For the development of the work, an analysis was made of the structure of the mentioned building with the purpose of verifying its dimensions to start the study. Soil resistivity measurements were also carried out in order to carry out the stratification and to do the grounding study. The results obtained are important for the accomplishment of the projects, soon those that are essential for any large building.
Monografia
Keywords: Aterramento; SPDA; Resistividade; Prédios públicos; Proteção; Descargas Atmosféricas; Grounding; SPDA; Resistivity; Protection; Atmospheric Discharge; Public buildings; ENGENHARIAS::ENGENHARIA ELETRICA